ODE No. 620

\[ y'(x)=\frac {e^{2 F((y(x)-x) (y(x)+x))}+x^2+2 x y(x)+y(x)^2}{-e^{2 F((y(x)-x) (y(x)+x))}+x^2+2 x y(x)+y(x)^2} \] Mathematica : cpu = 0.802721 (sec), leaf count = 205

DSolve[Derivative[1][y][x] == (E^(2*F[(-x + y[x])*(x + y[x])]) + x^2 + 2*x*y[x] + y[x]^2)/(-E^(2*F[(-x + y[x])*(x + y[x])]) + x^2 + 2*x*y[x] + y[x]^2),y[x],x]
 

\[\text {Solve}\left [\int _1^{y(x)}\left (-\frac {2 K[2]}{-x^2+e^{2 F((K[2]-x) (x+K[2]))}+K[2]^2}-\int _1^x\left (\frac {2 K[1] \left (-4 e^{2 F((K[2]-K[1]) (K[1]+K[2]))} F'((K[2]-K[1]) (K[1]+K[2])) K[2]-2 K[2]\right )}{\left (K[1]^2-e^{2 F((K[2]-K[1]) (K[1]+K[2]))}-K[2]^2\right )^2}-\frac {1}{(K[1]+K[2])^2}\right )dK[1]+\frac {1}{x+K[2]}\right )dK[2]+\int _1^x\left (\frac {1}{K[1]+y(x)}-\frac {2 K[1]}{K[1]^2-e^{2 F((y(x)-K[1]) (K[1]+y(x)))}-y(x)^2}\right )dK[1]=c_1,y(x)\right ]\] Maple : cpu = 0.246 (sec), leaf count = 37

dsolve(diff(y(x),x) = (y(x)^2+2*x*y(x)+x^2+exp(2*F(-(x-y(x))*(y(x)+x))))/(y(x)^2+2*x*y(x)+x^2-exp(2*F(-(x-y(x))*(y(x)+x)))),y(x))
 

\[y \left (x \right ) = {\mathrm e}^{\RootOf \left (-\textit {\_Z} +\int _{}^{{\mathrm e}^{2 \textit {\_Z}}-2 \,{\mathrm e}^{\textit {\_Z}} x}\frac {1}{{\mathrm e}^{2 F \left (\textit {\_a} \right )}+\textit {\_a}}d \textit {\_a} +c_{1}\right )}-x\]